The application of time-flow curves in hydropower calculations - Sławomir Bajkowski (Acta Scientiarum Polonorum. Formatio Circumiectus)
Curves developed by hydrologists are used to assess energy resources of rivers, and determine installation parameters of hydroelectric plants. They facilitate the determination of the flows’ value, as well their long-term, annual and seasonal volatility. The installation flow rates of small-scale lowland hydroelectric plants are determined on the basis of the energy resources of watercourses, the value of net head streams and the criteria of economic feasibility of the investment. The article presents the method of applying time–flow curves in order to determine the installation flow rate of small-scale lowland hydropower plants. The analysis was carried out for the projected flows, and for the flows assumed in the development of water energy cadastre. The effective head stream was assumed as a constant unit value, presupposing the same changes in the upper and lower water level. The obtained values of annual installation flow rates were referred to the mean values of annual flow in the base years, and the mean flow in the multiyear period. The rate of growth and the amount of available energy constitute suitable criteria for the selection of installation flow rate in small-scale hydropower plants.